2018
DOI: 10.3389/fnins.2018.00563
|View full text |Cite
|
Sign up to set email alerts
|

WWOX Phosphorylation, Signaling, and Role in Neurodegeneration

Abstract: Homozygous null mutation of tumor suppressor WWOX/Wwox gene leads to severe neural diseases, metabolic disorders and early death in the newborns of humans, mice and rats. WWOX is frequently downregulated in the hippocampi of patients with Alzheimer’s disease (AD). In vitro analysis revealed that knockdown of WWOX protein in neuroblastoma cells results in aggregation of TRAPPC6AΔ, TIAF1, amyloid β, and Tau in a sequential manner. Indeed, TRAPPC6AΔ and TIAF1, but not tau and amyloid β, aggregates are present in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
67
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(68 citation statements)
references
References 130 publications
1
67
0
Order By: Relevance
“…WWOX expression is relatively strong in human, rat and mouse neural tissues, and varies according to the location [19,34,53,61]. Notably, WWOX may interact with steroid hormone 17β-estradiol via its NSYK (Asn-Ser-Tyr-Lys) motif in the C-terminal short-chain alcohol dehydrogenase/reductase domain for neuroprotection [42]. Whether WWOX acts as a receptor for steroid hormones for initiating neuroprotective signaling pathways and promoting cerebellum development is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…WWOX expression is relatively strong in human, rat and mouse neural tissues, and varies according to the location [19,34,53,61]. Notably, WWOX may interact with steroid hormone 17β-estradiol via its NSYK (Asn-Ser-Tyr-Lys) motif in the C-terminal short-chain alcohol dehydrogenase/reductase domain for neuroprotection [42]. Whether WWOX acts as a receptor for steroid hormones for initiating neuroprotective signaling pathways and promoting cerebellum development is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the above studies, disease mechanisms by which loss of Wwox leads to WOREE-associated CNS alterations have not been fully understood yet. Different hypotheses have been proposed, including abnormal tau phosphorylation, mitochondrial dysfunction, altered cell differentiation, and neuronal apoptosis (Ramos and Aldaz, 2006;Aldaz et al, 2014;Liu et al, 2018). To investigate the impact of Wwox deficiency on human brain developmental processes, we performed brain histopathological analyses of the 21th week aborted fetus (II.3) with WOREE syndrome and identified abnormal architecture of the developing cerebral cortex.…”
Section: Discussionmentioning
confidence: 99%
“… 54 57 The hyperphosphorylated Tau molecules aggregate and form NTFs, thus restricting neurite outgrowth and preventing neuronal differentiation. 58 In addition, WWOX can also physically bind Tau protein by its SDR domain and stabilize it. 54 This regulation of Tau phosphorylation is important not only in the context of neurodegeneration, but also neuronal differentiation, where the Tau protein takes part in microtubule assembly and neurite outgrowth.…”
Section: Neurodegenerationmentioning
confidence: 99%
“…It has been found that WWOX prevents TPC6AΔ and TIAF1 aggregation by physically interacting with them. 58 In vitro stimulation with TGFβ results in the dissociation of WWOX from the complex and the initiation of the protein aggregation cascade. TPC6AΔ and Tau plaques were found in the brain cortex of WWOX knockout mice as early as in the first three weeks of life, and WWOX-depleted mouse embryonic fibroblasts (MEF) contain aggregates of TPC6AΔ, TIAF1, JNK1, and Tau tangles.…”
Section: Neurodegenerationmentioning
confidence: 99%